Leiomyosarcoma of the inferior vena cava: Radical surgery and vascular reconstruction - Alexander, Andrea (BioMed Central, 2009)
BACKGROUND: Vascular leiomyosarcoma are rare tumors typically originating from the inferior vena cava (IVC). Due to nonspecific clinical signs most tumors are diagnosed at advanced stages. Complete surgical resection remains the only potential curative therapeutic option. Surgical strategy is particularly influenced by the level of the IVC affected. Due to the topographic relation to the renal veins level-II involvement of the IVC raises special surgical challenges with respect to the maintenance of venous outflow. CASE PRESENTATION: We herein report two cases of leiomyosarcoma of the IVC with successful en bloc resection and individualized caval reconstruction. One patient presented with a large intramural and intraluminal mass and received a complete circumferential resection. Reconstruction was performed by graft replacement of the caval segment affected. The other patient displayed a predominantly extraluminal tumor growth and underwent semicircumferential resection of the IVC including the confluence of the left renal vein. In this case vascular reconstruction was performed by cavoplasty and reinsertion of the left renal vein into the proximal portion of the IVC. Resection margins of both patients were tumor free and no clinical signs of venous insufficiency of the lower extremity occurred. CONCLUSION: This paper presents two cases of successfully managed leiomyosarcomas of the vena cava and exemplifies two different options for vascular reconstruction in level II sarcomas and includes a thorough review of the literature.